Dynamics of seedling growth of Vitex parviflora Juss compost substrates bark of Eucalyptus saligna Smith and Eucalyptus pellita F. Muell in forest nurseries - Noarys Pérez Díaz (Revista Cubana de Ciencias Forestales, 2014)
The successful formation of high forest production depends largely on the quality of seedlings, which must withstand the harsh conditions encountered in the field and produce economically desirable trees with volumetric growth. To evaluate the growth dynamics of Vitex parviflora Juss seedlings in bark compost substrates of Eucalyptus saligna Smith and Eucalyptus pellita F. Muell in nurseries is the objective. Substrates in which the seedlings were developed compost made from bark of Eucalyptus saligna Smith and Eucalyptus pellita F. Muell, mixed with peat in different proportions. The seedlings were evaluated in nurseries morphological characteristics; allowing to determine its growth dynamics and morphological indices that characterize them. Which demonstrated that there, during the growth of plants Vitex parviflora Juss in the substrates studied in the nursery stage an establishment phase, with duration, about 45 days after planting a rapid growth phase, with a duration of approximately 50 days, after the phase establishment and hardening phase approximately 95 days after planting and morphological parameters of plants obtained Vitex parviflora Juss showed no major significant differences between them although the best results were for plants grown in compost substrates without extracting.